Morphologies of thienyl based bimetallic metal-organic frameworks controlled by solvents for high specific capacitance supercapacitor. (March 2022) - Song, Senyang; Ma, Xiaoyan; Zhang, Boyuan; Li, Wenyue; Feng, Yusen; Tan, Chenglong
Highlights: Thienyl based bimetallic Ni/Co MOF was synthesized with different solvents through solvothermal process. The degree of solvent protonation can effectively control the morphology and structure of NCT MOF. Ethanol solvent is favorable for high electrochemical performance of NCT-MOF. . The capacity retention of supercapacitor device is 82.75% after 5000 cycles. Abstract: Metal-organic frameworks(MOF) is a promising energy storage material, but its low electron transmission efficiency and low energy density hinder its application as a high-performance supercapacitor electrode material. Here, we show a Ni/Co bimetallic MOF electrode based on thiophene ligand with diverse morphologies from solvothermal method utilized different solvents. The results showed that the morphology of thienyl based Ni/Co MOF gradually changes from a spherical structure to a flaky structure as the degree of solvent protonation increases. Compared with other MOFs synthesized by low protonation solvent, thienyl based Ni/Co MOF with a sheet-like structure synthesized by ethanol provides more paths for electron transport between layers, and more activity for ion migration on the electrode surface site, ensuring a higher charge storage capacity. The electrochemical performance of thienyl based Ni/Co MOF as supercapacitor electrode materials in 1 M KOH was assessed, and it is found that when the current density is 1 A g −1, the maximum specific capacitance of thienyl based Ni/Co MOF(synthesized by ethanol) is 1282 F g −1, and the capacitance retention rate of asymmetric supercapacitor device assembled by thienyl based Ni/Co MOF(synthesized by ethanol) is about 73.6% even after 10, 000 cycles, meaning that thienyl based Ni/Co MOF(synthesized by ethanol) is a promising electrode material for supercapacitors. Graphical abstract: Image, graphical abstract